Representasi Bentuk Cyberbullying dalam Media Sosial Instagram (Analisis Semiotika pada Akun @rachelvennya) - Hafshah Hazimah; Hariyanto, Didik (Jurnal Spektrum Komunikasi, 2023)
As the world of technology develops, communication patterns also evolve. This is marked by the emergence of new media known as social media. The use of social media also has negative effects, one of which is the phenomenon of cyberbullying. Instagram is one of the social media platforms where this phenomenon occurs the most. Like Rachel Vennya, an influencer as well as a public figure who has experienced cyberbullying on her Instagram account. This study aims to analyze the verbal and non-verbal meanings of posting images and language text comments on the Instagram account @rachelvennya based on Ferdinand de Saussure's semiotic theory. The research method used is a qualitative approach with a descriptive research type. Data collection is done by making observations and observations, assisted by documentation. The research results show that 5 different Rachel Vennya Instagram posts reap negative comments that contain elements of cyberbullying. And 5 of these posts have different forms of cyberbullying, 2 of which are sexual harassment, and the other 3 posts are harassment / humiliation, and satire. Conclusion: The impact of this cyberbullying action is to limit the comment column on the @rachelvennya Instagram account. And the language used by cyberbullies seems harsh, frontal and impolite